When Words Become Difficult: A Critical Reflection of the ‘MeBox’ Method in Understanding Senior Travellers’ Responses to Loss - Ramanayake, Uditha; Cockburn-Wootten, Cheryl; McIntosh, Alison (Edward Edgar Publishing, 2021)
Multiple dimensions of our experiences such as visual, embodied and sensory experiences cannot always be easily expressed in words. Traditional qualitative methods may struggle to access these deep-rooted complex and emotional aspects. Tourism scholars have called for innovative methodologies to unravel layers of diverse meaning in phenomena. This article critically reflects on a visual tool called the ‘MeBox’. It was adopted in our study to explore senior travellers’ responses to loss following a major life event. The ‘MeBox’ method enabled participants to express embedded and tacit knowledge to reflect on their lived experiences. We critically review the ‘MeBox’ methodology, and provide practical learnings for scholars who may want to adopt this method as a means to under-stand lived experiences that are difficult to express in words.